Phylogeny, taxonomy and flower-breeding ecology of the Colocasiomyia cristata species group (Diptera: Drosophilidae), with descriptions of ten new species - Takano, Kohei Takenaka; Gao, Jian-Jun; Hu, Yao-Guang; Li, Nan-Nan; Yafuso, Masako; Suwito, Awit; Repin, Rimi; Pungga, Runi Anak Sylvester; Meleng, Paulus Ak; Kaliang, Clement Het; Chong, Lucy; Toda, Masanori J. (Zootaxa, 2021)
The phylogeny of the Colocasiomyia cristata species group is reconstructed as a hypothesis, based on DNA sequences of two mitochondrial and six nuclear genes and 51 morphological characters. The resulting tree splits this species group into two clades, one of which corresponds to the colocasiae subgroup. Therefore, a new species subgroup named as the cristata subgroup is established for the other clade. Within the cristata subgroup, three subclades are recognized and each of them is defined as a species complex: the cristata complex composed of five species (including three new ones: C. kinabaluana sp. nov., C. kotana sp. nov. and C. matthewsi sp. nov.), the sabahana complex of two species (C. sabahana sp. nov. and C. sarawakana sp. nov.), and the xenalocasiae complex of five species (including C. sumatrana sp. nov. and C. leucocasiae sp. nov.). There are, however, three new species (C. ecornuta sp. nov., C. grandis sp. nov. and C. vieti sp. nov.) not assigned to any species complex. In addition, breeding habits are described for four cristata-subgroup species, each of which monopolizes its specific host plant. And, data of host-plant use are compiled for all species of the cristata group from records at various localities in the Oriental and Papuan regions. The evolution of host-plant selection and sharing modes is considered by mapping host-plant genera of each species on the phylogenetic tree resulting from the present study.